Paradigma Baru Pelaksanaan Investasi Pemerintah Pusat dalam Perspektif Hukum Keuangan Negara - Tambunan, Gerry Maranatha (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Government investment as one of the instruments of the central government in relation to the management of state finances began to be publicly introduced with the issuance of Law Number 1 of 2004 concerning State Treasury. Government investment is carried out to obtain economic benefits, social benefits and other benefits for the implementation of national development aimed at achieving social welfare for all Indonesian people as mandated in the 1945 Constitution of the Republic of Indonesia. Government investment is not only one of the tools. in national development, but moreover it becomes the main instrument in running the economy of the Indonesian nation considering that the implementation of government investment is carried out in various forms of investment instruments in the form of stocks, debt securities and / or direct investment whose financing is allocated in the State Revenue and Expenditure Budget. This journal explains the implementation of government investment carried out by the Minister of Finance as the current State General Treasurer based on existing laws and regulations in the perspective of state financial law